Optimization of Anti-kinking Designs for Vascular Grafts Based on Supramolecular Materials - Wu, Dan Jing; van Dongen, Kim; Szymczyk, Wojciech; Besseling, Paul J.; Cardinaels, Ruth M.; Marchioli, Giulia; van Genderen, Marcel H. P.; Bouten, Carlijn V. C.; Smits, Anthal I. P. M.; Dankers, Patricia Y. W. (Frontiers in Materials, 2020)
Synthetic vascular grafts to be applied as access grafts for hemodialysis often require anti-kinking properties. Previously, electrospun microporous vascular implants based on synthetic supramolecular materials have been shown to perform adequately as resorbable grafts due to the microstructures, thereby enabling attraction of endogenous cells and consecutive matrix production in situ. Here, we use supramolecular materials based on hydrogen bonding interactions between bisurea (BU) or 2-ureido-4[1H]-pyrimidinones (UPy) to produce microporous anti-kinking tubular structures by combining solution electrospinning with 3D printing. A custom-made rational axis for 3D printing was developed to produce controlled tubular structures with freedom in design in order to print complex tubular architectures without supporting structures. Two different tubular grafts were developed, both composed of a three-layered design with a 3D printed spiral sandwiched in between luminal and adventitial electrospun layers. One tubular scaffold was composed of BU-polycarbonate electrospun layers with 3D printed polycaprolactone (PCL) strands in between for dimensional stability, and the other graft fully consisted of supramolecular polymers, using chain-extended UPy-PCL as electrospun layers and a bifunctional UPy-PCL for 3D printing. Both grafts, with a 3D printed spiral, demonstrated a reproducible dimensional stability and anti-kinking behavior under bending stresses.